The integration of work ethics and technology acceptance towards enhancing online learning environment among lecturers - Aziz, Faiq; Md Rami, Aizuddin; Mohd Rasdi, Roziah; Nurfazreen Aina (Science Research Society, 2021)
The adoption of online learning environment has become one of the major concerns in education industry due to the advancement of technology. Even though institutions and organizations had invested huge amount to ensure the online learning platform can be beneficial towards lecturers and other users, however, the progress in solving the issue remained sluggish. Nevertheless, the existing models and theory pertaining to intention and behavior towards adopting online learning is not sufficiently taken into account in the current studies. In this essence, work ethics are important as a guideline to proper everyday professional life which assists employees to grow professional codes of ethics that define professional standards for conduct. Hence, workers possessing a great work ethic have instilled principles that steer the way they behave at workplace. Considering this, this paper aims to form a model integration of work ethics acts as an antecedent of performance expectancy, effort expectancy, social influence, and facilitating conditions in the UTAUT model which can lead towards the intention of adopting online learning environment. The proposed concept would develop theoretical framework based on integration model. Hence, this study will produce a new theoretical framework model that integrate work ethics with UTAUT for enhancing online learning approach among lecturers using technology and will contribute towards preparing future learning environment that equip with technology advancement and crafting training and development of online learning environment in line Industrial Revolution 4.0 in Malaysia.